Fast and stable lithium-ion storage kinetics of anatase titanium dioxide/carbon onion hybrid electrodes. Issue 20 (8th May 2018) - Lim, Eunho; Shim, Hwirim; Fleischmann, Simon; Presser, Volker
Abstract : In this work, we report on nanosized anatase TiO2 /carbon onion hybrid materials (nano-TiO2 –C) as a rapid and stable lithium insertion host easily synthesized by tailored sol–gel chemistry. Abstract : Research on alternatives to replace conventional graphite anodes is needed to advance lithium-ion battery technology. In this work, an anatase nano-TiO2 /carbon onion hybrid material (nano-TiO2 –C) is introduced as a rapid and stable lithium storage anode material, synthesized by a simple synthetic route using tailored sol–gel chemistry. The nano-TiO2 –C hybrid material provides highly reversible capacity (166 mA h g −1 at 0.02 A g −1 ), promising rate capability (61 mA h g −1 at 5 A g −1 ), and long-term cycle stability (capacity retention: 94% at 1 A g −1 for 1000 cycles). We demonstrate that hybridization of nano-TiO2 with carbon onions improves the high rate performance significantly.